Effect of bispecific recombinant oncolytic adenovirus carrying apoptin on apoptosis of MCF-7 cells - Chen, Shuang; Li, Wenyao; Yin, Xunzhe; Hu, Cheng; Li, Yiquan; Shao, Xiaotong; Li, Xiao; Jin, Ningyi (Frontiers in Immunology, 2025)
ObjectiveIn this study, breast cancer cell line MCF-7 was infected with recombinant oncolytic adenovirus Ad-VT expressing apopsin protein, and its anti-tumour pathway was detected to determine its possible anti-tumour signalling pathway.MethodIn this study, the inhibitory effect of recombinant oncolytic adenovirus Ad-VT on breast cancer cells was investigated through cell activity experiment and establishment of tumour bearing model in mice. Subsequently, in order to determine the apoptosis-inducing effect of recombinant oncolytic adenovirus on breast cancer cells, the effects of three recombinant oncolytic adenovirus on the apoptosis-inducing level of breast cancer cells were further analysed by Annexin V-FITC/PI detection, Hoechst staining, JC-1 staining and transmission electron microscopy. Then the differentially expressed proteins associated with apoptosis and possible signalling pathways were identified by proteomics and WB experiments.ResultsIn vivo and in vitro experiments showed that recombinant oncolytic adenovirus Ad-VT expressing apoptosis protein could induce apoptosis and inhibit the growth of MCF-7 cells. Proteomic analysis showed that differential genes were enriched in mTOR, MAPK and other pathways after Ad-VT infection of breast cancer cells, and the expression of S6K genes related to mTOR pathway was significantly increased in differential gene analysis, subsequently, the high expression of phosphorylated mTOR and S6K proteins was also determined by WB experiment, suggesting that Ad-VT may regulate the apoptosis of breast cancer cells through mTOR/S6K signalling.ConclusionAd-VT can significantly increase the apoptosis level of breast cancer cells, which may be induced by the mTOR/S6K signalling pathway. The results of this study provide a theoretical basis for the development of anti-tumour drugs based on Ad-VT in the future.